PENGARUH PENGUNGKAPAN TERKAIT KEBERLANJUTAN DAN IKLIM SESUAI IFRS S1 DAN S2 TERHADAP NILAI PERUSAHAAN - Dwiyandi, Nando (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
Sustainability disclosure is entering a new era with the enhanced integration of sustainability and climate-related practices into corporate business and financial models through the newly established IFRS S1 and S2 Standards, which the International Sustainability Standards Board introduced in mid-2023 and take effect with implementation set for the 2024 reporting year. With focusing on companies listed in the ESG Quality 45 IDX KEHATI Index, this study will examines whether firm values can be influenced by sustainability and climate-related core content disclosures under these Standards. The research employs a quantitative model using Random Effects Model with multiple linear regression equations. The results reveal that firm value is significant-negatively influenced by governance and strategy disclosures. Risk management disclosures can positively influence the firm value. However, firm value can not be influenced by metrics and targets disclosures. The research findings suggest that companies must strengthen their knowledge base and competencies in aligning these four core contents to achieve comprehensive and transparent sustainability disclosure.